Update on the implication of potassium channels in autism: K+ channelautism spectrum disorder - Guglielmi, Luca; Servettini, Ilenio; Caramia, Martino; Catacuzzeno, Luigi; Franciolini, Fabio; D’Adamo, Maria Cristina; Pessia, Mauro (Frontiers in Cellular Neuroscience, 2015)
Autism spectrum disorders (ASDs) are characterized by impaired ability to properly implement environmental stimuli that are essential to achieve a state of social and cultural exchange. Indeed, the main features of ASD are impairments of interpersonal relationships, verbal and non-verbal communication and restricted and repetitive behaviors. These aspects are often accompanied by several comorbidities such as motor delay, praxis impairment, gait abnormalities, insomnia and above all epilepsy. Genetic analyses of autistic individuals uncovered deleterious mutations in several K+ channel types strengthening the notion that their intrinsic dysfunction may play a central etiologic role in ASD. However, indirect implication of K+ channels in ASD has been also reported. For instance, loss of fragile X mental retardation protein (FMRP) results in K+ channels deregulation, network dysfunction and ASD-like cognitive and behavioral symptoms. Therefore, this review provides an update on direct and indirect implications of K+ channels in ASDs. Owing to a mounting body of evidence associating a channelopathy pathogenesis to autism and that nearly 500 ion channel proteins are encoded by the human genome, we also propose to classify ASDs − whose susceptibility is significantly enhanced by ion channels defects, either in a monogenic or multigenic condition − in a new category named “channelAutism Spectrum Disorder” (channelASD; cASD) and introduce a new taxonomy (e.g.: Kvx.y-channelASD and likewise Navx.y-channelASD, Cavx.y-channelASD; etc.). This review also highlights some degree of clinical and genetic overlap between K+ channelASDs and K+ channelepsies, whereby such correlation suggests that a subcategory characterized by a channelASD-channelepsy phenotype may be distinguished. Ultimately, this overview aims to further understand the different clinical subgroups and help parse out the distinct biological basis of autism that are essential to establish patient-tailored treatment